1991
DOI: 10.1007/bf01131588
|View full text |Cite
|
Sign up to set email alerts
|

Combined gonadotropin releasing hormone agonist/human menopausal gonadotropin therapy (GnRH-a/hMG) in normal, high, and poor responders to hMG

Abstract: Patients who failed to conceive after gonadotropin stimulation in in vitro fertilization treatment were classified into normal, high, or poor responders. They were routinely offered another cycle with a combination of a gonadotropin releasing hormone agonist and gonadotropin therapy (in order to evaluate whether this combined therapy could improve their response). The gonadotropin-induced cycle was compared with the combined therapy cycle. With the combination treatment, in the normal responders the phase of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Some studies demonstrated that adding E2 supplementation in luteal phase could not significantly affect patients' hormone profile [10], histological pattern of the endometrium [1] or estrogen receptors [3]. It seems that the optimal E2 level is not the same in different patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated that adding E2 supplementation in luteal phase could not significantly affect patients' hormone profile [10], histological pattern of the endometrium [1] or estrogen receptors [3]. It seems that the optimal E2 level is not the same in different patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, assisted reproductive technology (ART) is so popular in treatment of infertility, but the main problem in these methods is treatment of poor responder patients [1]. The rates of poor ovarian responses to the stimulation have been reported from 9% to 24% [2,3] leading to a low pregnancy rate in these patients (about 2%-4%) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Poor response was defined as [1] at least two failed IVF cycles with <5 oocytes (14), [2] estradiol (E 2 ) <500 pg/mL on day of hCG and <3 oocytes retrieved in a previous IVF cycle (15), [3] %2 oocytes retrieved or R48 ampoules of human menopausal gonadotropins (hMG) consumed in R2 previous cycles (16), [4] <6 oocytes collected, of which <4 embryos developed in at least one previous IVF cycle (17), and [5] previous suboptimal response (not defined by the investigators) to ovarian stimulation for IVF (18).…”
Section: Interventions Identified For Improving the Probability Of Prmentioning
confidence: 99%
“…Currently the percentage of poor responders, out of all infertile patients undergoing IVF-ET programs, is varies from 9% to 24% [2,3]. Poor responders include women in whom a previous cycle yielded three or fewer oocytes or was cancelled because of observations of three or fewer follicles 16 mm or greater, a single dominant follicle or a peak serum estradiol less than 500 pg/ml.…”
Section: Introductionmentioning
confidence: 99%